ANALISIS PERMINTAAN TELUR BERDASARKAN JENIS DAN STRATA PENDAPATAN DI KALIMANTAN SELATAN - Suslinawati Suslinawati; Masyhuri Masyhuri; Mas Soedjono (Agro Ekonomi, 2001)
This research wanted to know the consumer behavior in demand of egg as source of animal protein in South Kalimantan. In particular, this research aimed to identify and to know the price elasticity, cross elasticity and income elasticity at low, middle and high income groups, which were divided into the rural and urban areas and also were divided into egg of layer, "buras" and duck.The data that was used in this research was SUSENAS data 1996, with 1698 surveyed households. The analysis used TOBIT model or the censored regression model. TOBIT model is a regression model that was used to estimate the qualitative difference between limit observation (zero) and non-limit observation (continuous).The result also showed that generally, the characteristic of demand of egg based on SUSENAS data 1996 in South Kalimantan was in-elastic except on demand of egg at low income stratum in rural area and on demand of egg of "buras", where the both of them were elastic. In accordance with SUSENAS data 1996, for South Kalimantan society, egg was normal good since all estimations showed that income elasticity was higher than zero and smaller than one